The role of ants in minesite restoration in the Kakadu region of Australia's Northern Territory, with particular reference to their use as bioindicators - Andersen, Alan N. (Alan Neil), 1957- (Supervising Scientist Report, 1998)
The goal of land rehabilitation following mining in environmentally sensitive areas is often ecosystem restoration, rather than simply revegetation. This is the case at Ranger uranium mine (RUM) in the Alligator Rivers Region of Australia's Northern Territory. Effective methods of monitoring ecological restoration are therefore required. Ants have frequently been used as indicators of restoration success following mining in northern Australia, but the extent to which ants actually provide a reliable indication of ecological change has been poorly documented. This study aimed, primarily, to investigate the degree to which ants provide an indication of the general status of ecosystems and, secondarily, to examine the direct role of ants in ecosystem restoration.